DOES WEBSITE APPEARANCE AFFECT PURCHASE INTENTION? - Tiara Melati Putri; R.A. Marlien (Jurnal Ekonomi, 2023)
One form of consumer behavior is the interest or desire to purchase a product or service. The purpose of this research is to determine the influence of website appearance and promotion on purchase intention mediated by trust. The population in this study is Shopee application users in the Semarang City area. The sample size is 112, using purposive sampling technique. The findings show that website appearance and promotion have a positive and significant effect on trust. Website appearance, promotion, and trust partially have a positive and significant effect on purchase intention. Trust can be a mediating variable for the influence of website appearance and promotion on consumer purchase intention.